Spark plasma sintering of W-10Ti alloys: microstructure, properties and grain growth kinetics. (30th April 2021) - Xu, Wenfei; Huang, Lei; Peng, Tianshuai; Pan, Yafei; Zhang, Jiuxing; Zhang, Shuyan
Abstract: The microstructure, properties and grain growth kinetics of W-10 wt.% Ti alloys prepared by spark plasma sintering (SPS) method at the temperatures from 1400 to 1700 °C, with the dwelling time from 0 to 30 min and a constant axial pressure of 30 MPa were investigated. The sintered W-10Ti alloys only contained a dominant β -W(Ti) phase and a fractional β -Ti(W) phase. The content of Ti-rich phase declined with the rise of sintering temperatures. In addition, the higher the sintering temperature, the higher the alloy density. When the sintering temperature was constant, the alloy density first increased and then decreased with the increasing dwelling time, and reached the maximum at 15 min. With the increase of the sintering temperature and dwelling time, the thermal conductivity first decreased, then flattened or slightly increased. At low temperatures (1400 °C–1500 °C), the grain growth was not obvious, but at high temperatures (1600 °C–1700 °C), the grain grew rapidly. The grain growth exponent of W-10Ti alloys was found to be n  = 2, suggesting grain boundary diffusion controlled grain growth in the alloys. Activation energy for grain growth was calculated as 49.21–61.46 kJ mol −1 .